Pembuatan dan Upaya Peningkatan Kualitas Pupuk Organik Cair - Dedy Prasetyo; Rusdi Evizal (JURNAL AGROTROPIKA, 2021)
Conventional agricultural practices are very intensively utilizing synthetic agrochemicals. The resulting impact is a decrease in soil quality, thereby reducing fertilizer efficiency and plant yield. Efforts to maintain soil health include restoring organic matter. Organic fertilizers can be produced by utilizing the surrounding agricultural waste. Liquid organic fertilizer (LOF) can be produced from organic waste which should be chosen from high content of macro nutient. The quality of LOF could be increased by adding commercial decomposer starter or local microorganism. Organic matter of high energy should be added as well. The process of making liquid organic fertilizer is involved a fermentation process. Microbes will decompose organic material by breaking down the nutrients in the material to dissolve in solution. POC applications have been tested on various agricultural commodities. The provision of POC can increase the growth and yield of plants. In addition, the use of POC can improve soil health. Keywords : fermentation, fruit, industry, microbe, LOF, pulp, quality, vegetable, waste